The Val Shirreff Memorial Lecture The New Millennium: a Surgical Odyssey - Lemire, Ginette (Operating Room Nurses Association of Canada Journal, 2001)
I am delighted to join you for your national conference to present the keynote address and to have the opportunity to meet many of you, particularly in this wonderful rocky mountains setting.